2006
DOI: 10.1371/journal.ppat.0020023
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus MicroRNAs Are Evolutionarily Conserved and Differentially Expressed

Abstract: The pathogenic lymphocryptovirus Epstein–Barr virus (EBV) is shown to express at least 17 distinct microRNAs (miRNAs) in latently infected cells. These are arranged in two clusters: 14 miRNAs are located in the introns of the viral BART gene while three are located adjacent to BHRF1. The BART miRNAs are expressed at high levels in latently infected epithelial cells and at lower, albeit detectable, levels in B cells. In contrast to the tissue-specific expression pattern of the BART miRNAs, the BHRF1 miRNAs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
601
3
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(650 citation statements)
references
References 51 publications
43
601
3
3
Order By: Relevance
“…All of the herpesviruses analyzed until now express miRNAs and, in particular, EBV is known to encode 420 miRNAs (Cai et al, 2006;Grundhoff et al, 2006;Gurtsevitch, 2008;Cullen, 2009) that are differentially expressed in the different phases of the viral life cycle and between types of latency (Cai et al, 2006). EBVencoded miRNAs regulate both host and viral genes, hence an investigation of these relationships is very important for our understanding of the biological processes involved in viral latency, which could be exploited to design strategies for combating potential harm to the host (Pfeffer et al, 2004;Nair and Zavolan, 2006;Scaria et al, 2006;Gottwein and Cullen, 2008).…”
Section: Epstein-barr Virusmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the herpesviruses analyzed until now express miRNAs and, in particular, EBV is known to encode 420 miRNAs (Cai et al, 2006;Grundhoff et al, 2006;Gurtsevitch, 2008;Cullen, 2009) that are differentially expressed in the different phases of the viral life cycle and between types of latency (Cai et al, 2006). EBVencoded miRNAs regulate both host and viral genes, hence an investigation of these relationships is very important for our understanding of the biological processes involved in viral latency, which could be exploited to design strategies for combating potential harm to the host (Pfeffer et al, 2004;Nair and Zavolan, 2006;Scaria et al, 2006;Gottwein and Cullen, 2008).…”
Section: Epstein-barr Virusmentioning
confidence: 99%
“…Furthermore, DNA methylation associated with loss of expression in Akata Burkitt's lymphoma cells was found in the miR-BHRF1-1 located in the 5 0 -untranslated region of the BamH1 fragment H rightward open reading frame 1 gene (BHFR1), which is one of the two main miRNA clusters in EBV (Pfeffer et al, 2004;Cai et al, 2006;Fernandez et al, 2009) (Figure 2). These results suggest that, in addition to its role in controlling the expression of protein-coding genes involved in viral latency, DNA methylation also mediates the regulation of miRNA expression.…”
Section: Viral Epigenomes In Human Tumorigenesis Af Fernandez and M Ementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that EBV miRNAs are central mediators of viral gene expression, but recently experiments have demonstrated that MIR-BART5 promotes host cell survival by targeting PUMA expression and contributes to the establishment of latent infection in nasopharyngeal carcinoma and EBV germinal center cells (Choy et al, 2008). Given that MIR-BARTs are abundantly expressed in epithelial cells latently infected with EBV but are less expressed in B cell lines (Cai et al, 2006), they may be important in epithelial carcinogenesis. Another recent study showed that PUMA is also mediated by cellular miRNAs, including miRNA 221/222, thereby inducing cell survival (Zhang et al, 2010).…”
Section: Mir-bart5 Suppresses Puma Expressionmentioning
confidence: 99%
“…EBV is now known to express in latently infected cells at least 17 distinct miRNAs that are originating from two clusters located in the introns of the viral BART and adjacent BHRF1 genes. Differential regulation of EBV miRNA expression is observed and implies distinct roles during infection of different human tissues (72). Recently, EBV LMP1 was discovered as a target for miRNAs derived from BART cluster 1.…”
Section: Viral Micrornasmentioning
confidence: 99%